Experimental benchmarking of CFD codes used in simulations of heat exchangers for nuclear-power applications - Bolshukhin, Mikhail Aleksandrovich; Vasiliev, Andrey Yurievich; Budnikov, Aleksey Vladimirovich; Patrushev, Dmitriy Nikolaevich; Romanov, Roman Igorevich; Sveshnikov, Dmitriy Nikolaevich; Sukhanovsky, Andrey Nikolaevich; Frick, Petr Gotlobovich (Computational Continuum Mechanics, 2012)
This study is aimed to provide benchmark experimental data for CFD codes used in simulations of heat-exchangers for nuclear-power applications. The experimental results obtained in studying turbulent Raleigh–Benard convection in a rectangular tank with dimensions(where one of the horizontal dimensions) are proposed as a benchmark. Experiments were carried out for a fixed Raleigh numberand different values of aspect ratio Гand 1. It has been found that, for these aspect ratios, the large-scale circulation is characterized by different regimes. Numerical simulations made by ANSYS CFX for two cases (Г,and Г,) provide relevant results not only for the mean flow but also for the spatial and temporal distribution of turbulent fluctuations. Long-time simulations are able to reproduce the dynamics of large-scale circulation, yet they require a remarkable increase of computation time for accurate comparison of flow characteristics.